Pulmonary rehabilitation improves functional outcomes and quality of life in post-SARS-CoV-2 mild-to-moderate infection patients: a pilot study - Guido Levi; Marco Umberto Scaramozzino; Stefania Cavallo; Giuliano Castignini; Michela Bezzi; Laura Pini; Frank Nania; Sheenam Sheenam (Monaldi Archives for Chest Disease, 2023)
SARS-CoV-2 infection impairs functional outcomes and quality of life, even in its mild-to-moderate form. It is therefore appropriate to draw attention to the role played by respiratory rehabilitation and physiotherapists in the pulmonary rehabilitation process that post-SARS-CoV-2 patients must undergo. We enrolled 80 patients in a prospective case-control study; 40 cases (mild-to-moderate post-SARS-CoV-2 infection patients) and 38 control subjects (i.e. patients affected by other respiratory diseases) completed a full pulmonary rehabilitation cycle. 6 Minute Walking Distance, Borg CR10 Scale, modified Medical Research Council (mMRC) Dyspnoea scale, EuroQoL EQ-5D-3L questionnaire, Barthel scale, arterial blood gas test and peripheral oxygen saturation (SpO2) were compared for all patients before and after rehabilitation. All patients experienced significant improvements in all parameters analyzed, except for arterial blood gas test. Results were similar for both groups, in particular both groups experienced improvements in mMRC scale, EuroQoL questionnaire, Barthel scale and 6-minute walking distance. Pulmonary rehabilitation appears to improve exercise tolerance, dyspnea and quality of life in patients recovering from mild-to-moderate SARS-CoV-2 infection. Further studies are needed on larger sample size population to validate these results.